The spirituality and spiritual care of clinical nurses in Indonesia - Rosnancy Renolita Sinaga; Donald Loffie Muntu; Sedia Simbolon; Sri Susanty (Intelektual Pustaka Media Utama, 2021)
This study aimed to investigate associated factors of spirituality and spiritual care in clinical nurses in Indonesia. Cross-sectional descriptive and correlational research designs were used in this study. Purposive sampling was applied among 204 participants in private hospitals, Medan and Bandung, Indonesia. The questionnaires consisted of demographic and characteristics information and the spirituality and spiritual care rating scale (SSCRS). Mann Whitney test was used to investigate associated factors of spirituality and spiritual care in clinical nurses in Indonesia. This study found that there was statistically significant between department with spirituality (p=0.017), receiving spiritual care lessons during nurse training with spiritual care (p=0.032), and receiving spiritual care lessons during nurse training (p=0.013) and educational background with nurses’ perception of spirituality and spiritual care (p=0.040). Receiving spiritual care lessons during nurse training, and educational background were statistically significant with spirituality and spiritual care in clinical nurses in Indonesia. The findings of this study provide information for clinical nurses and generally of nurses to understand the perception of spirituality and spiritual care in hospital for care patient in a hospital in Indonesia. It is also suggested that appropriate strategies to improve knowledge and perception of spirituality and spiritual care should be developed shortly.